Challenges for health systems in Member Countries of the Organisation for Economic Co-operation and Development - Hurst, Jeremy (2000)
Notes that for reasons of equity most OECD countries have chosen to base their funding of health care mainly on public sources. Opines that there is an almot universal problem of affordability in the health systems of these couontries, arising from the tension between the willingness of populations to pay taxes and the eagerness of patients to use health services where these are free or heavily subsidized at the point of use.